Taxonomic treatment of some Indian Magnolia L. in respect to Seedling Morphology. Issue 1 (10th October 2017) - Bose, Animesh; Das, Poushali; Paria, Nanda Dulal
Abstract : Seedling morphology of five species of Magnolia from different districts of West Bengal (India) were studied. The germination is epigeal, phanercotylar type. The seedlings are distinguishable on the basis of features like hypocotyl; shape, apex, and venation of paracotyledons; first two leaves and subsequent leaves have been considered also as key characters for the easy identification of the plants at juvenile stage. Similarities in seedling morphology rightly support the placement of Michelia under the genus Magnolia as treated recently. These taxa are facing various degrees of threats, mainly due to exploitation for their commercial potential as timber‐yielding plants, horticultural and medicinal plants. Consequently, conservation programmes of these plants can be planned through their identification at juvenile stages in natural sites.